(untitled) - Mock, Janet (New York, 2014)
In her profound and courageous New York Times bestseller, Janet Mock establishes herself as a resounding and inspirational voice for the transgender community--and anyone fighting to define themselves on their own terms.
Keywords: Người chuyển giới,Transgender people; Tiểu sử,Biography; Hoa Kỳ,United States